1969
DOI: 10.4141/cjps69-051
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Chemical Constituents and Morphological Characters Within and Between Alfalfa Populations

Abstract: A total af t26 atf^lf^otr".r, .trtfoT1l$o"" populations, were grown in three replicates-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 1 publication
1
23
0
Order By: Relevance
“…For instance, with the four-harvest data WL 322 had high DMY and IVDMD whereas Excalibur had low DMY and IVDMD (Table 3). Several studies also reported no correlation or weak correlations between digestibility and DMY when cultivars or lines were compared on a single sampling date corresponding to a normal harvesting date (Heinrichs et al 1969;Hill and Barnes 1977;Sunberg et al 1983;Coors et al 1986;Julier and Huyghe 1997). Other studies, however, reported a reduced forage DMY as a result of selection for improved nutritive quality (Kephart et al 1989).…”
Section: Relationship Among Variatesmentioning
confidence: 99%
“…For instance, with the four-harvest data WL 322 had high DMY and IVDMD whereas Excalibur had low DMY and IVDMD (Table 3). Several studies also reported no correlation or weak correlations between digestibility and DMY when cultivars or lines were compared on a single sampling date corresponding to a normal harvesting date (Heinrichs et al 1969;Hill and Barnes 1977;Sunberg et al 1983;Coors et al 1986;Julier and Huyghe 1997). Other studies, however, reported a reduced forage DMY as a result of selection for improved nutritive quality (Kephart et al 1989).…”
Section: Relationship Among Variatesmentioning
confidence: 99%
“…However, two alfalfa cultivars, differing for digestibility, induced differences in milk production of dairy cows (Emile et al, 1996(Emile et al, , 1997. Genetic variation for digestibility in alfalfa has been shown (Heinrichs et al, 1969;Buxton et al, 1987;Lenssen et al, 1991;Julier et al, 1996), and possibilities for improving populations have been demonstrated (Demment et al, 1986). Some data are available on changes in digestibility during plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…At Harvest 4 the contribution of stubble shoots was 21% and 33% for Moapa and Glutinosa respectively, the comparable figures for Harvest 7 being 15% and 26%. Glutinosa was thus similar to other falcata lucernes (Heinrichs et al 1969) in that internode lengths were appreciably shorter than those of the sativa type Moapa; thus Glutinosa had more stubble shoots below cutting height. The persistence of Glutinosa under grazing (Iversen 1967;White et al 1975) is probably due in part to these shorter internodes, which give more sites for shoot regeneration close to ground level.…”
Section: Differences Hetween Cultivarsmentioning
confidence: 60%
“…Much of the recent interest in lucerne as a pasture plant for grazing has been centred on the effects of higher proportions of Medicago falcata L. genes which confer wide crowns, increased rhizomatous development (Smith 1955), and shorter internodes (Heinrichs et al 1969). Leach (1969), working with spaced plants, showed that 'Totana', a sativa type (Iversen & Meijer 1967), had few large shoots which grew rapidly after lenient cutting.…”
Section: Introductionmentioning
confidence: 99%